Farnesol as an antifungal agent: comparisons among MTLa and MTLα haploid and diploid Candida albicans and Saccharomyces cerevisiae - Boone, Cory H. T.; Parker, Kory A.; Gutzmann, Daniel J.; Atkin, Audrey L.; Nickerson, Kenneth W. (Frontiers in Physiology, 2023)
Aims. Farnesol was identified 20 years ago in a search for C. albicans quorum sensing molecules (QSM), but there is still uncertainty regarding many aspects of its mode of action including whether it employs farnesol transport mechanisms other than diffusion. Based on the structural similarity between farnesol and the farnesylated portion of the MTLa pheromone, we explored the effects of ploidy and mating type locus (MTL) on the antifungal activity of exogenous farnesol.We approached this question by examining five MTLa and five MTLα haploid strains with regard to their farnesol sensitivity in comparison to six heterozygous MTLa/α diploids. We examined the haploid and diploid strains for percent cell death after exposure of exponentially growing cells to 0-200 µM farnesol. The heterozygous (MTLa/α) diploids were tolerant of exogenous farnesol whereas the MTLa and MTLα haploids were on average 2-and 4-times more sensitive, respectively. In the critical range from 10-40 µM farnesol their cell death values were in the ratio of 1:2:4. Very similar results were obtained with two matched sets of MATa, MATα, and MATa/α Saccharomyces cerevisiae strains.We propose that the observed MTL dependence of farnesol is based on differentially regulated mechanisms of entry and efflux which determine the actual cellular concentration of farnesol.The mechanisms by which pathogens such as C. albicans tolerate the otherwise lethal effects of farnesol embrace a wide range of physiological functions, including MTL type, ubiquinone type (UQ6-UQ9), energy availability, and aerobic/anaerobic status.